2013
DOI: 10.1603/ec12192
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gamma Sterilization on the Insecticidal Toxicity of Engineered and Conventional <I>Bacillus thuringiensis</I> Strains

Abstract: This study evaluates the effect of gamma radiation on the spore activity, toxicity, and crystal structures of two engineered Bacillus thuringiensis (Bt) strains, TnX and TnY, and the reference Bt strain HD-1. We attempted to identify dosages of cobalt-60 gamma radiation that would inactivate Bt spores but not affect its toxicity. In the radiation dosage range of 10-15 kilogray, no viable spore formation and no significant reduction of the efficiency of Bt against lepidopteran larvae were observed. However, fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
3
3
0
Order By: Relevance
“…It reduced by 20 and 29% for the pesticide irradiated at 20 and 25 kGy, respectively. These results are consistent with other research that irradiation at a dose of 20-25 kGy caused a 20-30% reduction in the effectiveness of Bt-based pesticide against mosquito larvae and the reduction of toxicity of Bt by radiation follows a rather linear model [5]. According to Sun et al, the insecticidal effectiveness of Bt products against lepidoptera pests did not reduce, but their toxicities against mosquito were significantly reduced by gamma irradiation [5].…”
Section: B Estimation Of Radiation Effect On the Toxicity Of Vbt Pesticidesupporting
confidence: 91%
See 2 more Smart Citations
“…It reduced by 20 and 29% for the pesticide irradiated at 20 and 25 kGy, respectively. These results are consistent with other research that irradiation at a dose of 20-25 kGy caused a 20-30% reduction in the effectiveness of Bt-based pesticide against mosquito larvae and the reduction of toxicity of Bt by radiation follows a rather linear model [5]. According to Sun et al, the insecticidal effectiveness of Bt products against lepidoptera pests did not reduce, but their toxicities against mosquito were significantly reduced by gamma irradiation [5].…”
Section: B Estimation Of Radiation Effect On the Toxicity Of Vbt Pesticidesupporting
confidence: 91%
“…From these results, the minimum dose required to sterilize the Bt spores in VBT was estimated as about 20 kGy, similar to the other results [4,12]. In studies on the radiation sensitivities of some Bacillus thuringiensis strains, Sun et al reported that 9, 12, 15 and 19 kGy were effective dose for killing 4 types of Bt spores particularly WP, HD-1, TnY and TnX spores, respectively [5]. The radiation sensitivities among the Bt strains depend on their physiological characteristics and their abilities to recover from radiation injury.…”
Section: Nd: Not Detectedsupporting
confidence: 80%
See 1 more Smart Citation
“…More recently, Sun et al. () reported that in the radiation dosage range of 10–15 kGy, no viable spore formation and no significant reduction in the efficiency of B. thuringiensis against lepidopteran larvae were observed, demonstrating that the use of gamma radiation is effective to inactivate the spores of engineered B. thuringiensis strains while preserving toxicity against the target insect larvae.…”
Section: Assessmentmentioning
confidence: 99%
“…SP7 isolate has spherical crystal protein form, SP15 from observation shows spherical crystal protein form. Other observation showed crystal proteins of spherical shape 15,16,17 . …”
Section: Figure 1compound Light Microscopephotograph Of (A) Sp7 Isolmentioning
confidence: 93%